Telelearning via the Internet. - Kouki, Rafa. (University of Ottawa (Canada), 1997)
The academic environment has been witnessing the rise of a new form of teaching and transferring knowledge; that is telelearning via the Internet. A certain number of problem areas are still facing telelearning practitioners, which should be worked an and resolved soon, if most of the expectations of a universal effective and successful telelearning environment are to be realized. Some of these issues include Internet security, copyrights of digital material, and accreditation of on-line degrees and programs. This thesis includes four parts. Part I includes a description of a variety of synchronous and asynchronous Internet tools, as well as their advantages and drawbacks. In part II, some case studies of Internet-based telelearning applications are described, in addition to a discussion of the results of two investigations about the current implementations of the Internet tools within a telelearning setting. Part III provides an analysis of the different economics of telelearning which comprises costs related to both: the students and the institution. Finally, in part IV a number of Internet issues relating to telelearning were examined. These include: security and policy issues such as copyright of on-line material, accreditation of on-line degrees and virtual institutions, on-line academic fraud, and evaluation of the Web's material.
Keywords: Education, Technology.